5 questions with: Mandy Pennington of Wilkes University. Issue 12 (20th February 2023) - Talarico, Donna
Abstract : We reached out to Mandy Pennington, Director of Digital Strategy at Wilkes University in Wilkes‐Barre, Pennsylvania, to ask her five questions and to learn what strategies have been successful for the central Pennsylvania college.